2019
DOI: 10.1016/j.biopsych.2018.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stress and Major Depressive Disorder on Hippocampal and Medial Prefrontal Cortex Morphology

Abstract: Volumetric reductions in the hippocampus and medial prefrontal cortex (mPFC) are among the most well documented neural abnormalities in major depressive disorder (MDD). Hippocampal and mPFC structural reductions have been specifically tied to MDD illness progression markers, including greater number of major depressive episodes (MDE), longer illness duration, and nonremission/treatment resistance. Chronic stress plays a critical role in the development of hippocampal and mPFC deficits, with some studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
246
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 389 publications
(261 citation statements)
references
References 150 publications
10
246
1
4
Order By: Relevance
“…[19][20][21] Mitochondria have been considered to play key roles in these changes in depression. [19][20][21] Mitochondria have been considered to play key roles in these changes in depression.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%
“…[19][20][21] Mitochondria have been considered to play key roles in these changes in depression. [19][20][21] Mitochondria have been considered to play key roles in these changes in depression.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%
“…Less gray matter volume and cortical thickness are also reported in the frontal cortex in subjects with mood disorders using magnetic resonance imaging by some investigators (see refs (Drevets et al, 1997;Bora and Pantelis, 2011;Belleau et al, 2018)), though not all (Bora and Pantelis, 2011;Gifuni et al, 2016;Rizk et al, 2018). Bora et al (2011) performed a metaanalysis of voxel-based morphometry from 23 studies involving 986 MDD patients and found cortical gray matter volume was reduced in rostral anterior cingulate cortex and dorsolateral and dorsomedial cortex as well as in hippocampus.…”
Section: Miguelmentioning
confidence: 99%
“…The smaller gray matter volume was related to illness duration leading the authors to conclude that chronic MDD has deleterious but regionally restricted effects on prefrontal cortex (ibid). The volume deficits related to the MDD, and also to stress (see (Belleau et al, 2018). It is not known, however, whether the reduced cortex thickness were attributable to the mood disorder, a suicide component of the psychopathy, or to both.…”
Section: Miguelmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we designed a protocol to investigate the effects on mice with depression-like behavior. Hippocampus, a region repeatedly implicated in the pathophysiology and depression progression [24], was chosen as our targeted brain region. It shows antidepressive-like effects in CUMS rodent model after a 5-day treatment.…”
Section: Introductionmentioning
confidence: 99%